Selective logging of a subtropical forest: Long-term impacts on stand structure, timber volumes, and biomass stocks - Bedrij, Natalia A.; Mac Donagh, Patricio M.; Putz, Francis E.; Genoveva Gatti, M. (Forest ecology and management, 2022)
•Subtropical Atlantic Forest recovered little commercial timber in 20-years post-logging.•Above-ground biomass of all trees recovered faster after CL than after RIL.•Mortality rates were high (4.4–6.3 % year−1) the first-year post-logging regardless of the harvest system applied.•Logging in this Subtropical Atlantic Forest is not sustainable even with RIL. Long-term studies are key to understanding the dynamics of managed forests, especially as related to timber supplies. We evaluated 20 years of recovery of pre-harvest structure, biomass, and timber stocks of a Subtropical Atlantic Forest in Argentina subjected to either conventional selective logging (CL = ∼15 m3 ha−1) or reduced-impact logging (RIL = ∼11 m3 ha−1); we also monitored the dynamics of interspersed plots of unlogged forest (Control). All trees ≥10 cm DBH were measured before and at variable intervals for 20 years post-logging; the results are presented for all stems and for only those of species that provide commercial timber. After logging, basal areas and volume of all stems increased two-times faster after CL than after RIL, whereas biomass increments were similar between logged treatments. In contrast, commercial timber tree stocking did not recover regardless of the harvesting system applied. Mortality rates were high in both CL and RIL plots but also in unlogged Control plots (1.6–3.6 % year−1). The failure of timber stocks to recover was apparently due to high tree mortality rates coupled with the proliferation of understory bamboos. Alternative silvicultural methods are clearly needed to avoid degrading the remaining species-rich Subtropical Atlantic Forest.